Marketing Maximilian: the visual ideology of a Holy Roman Emperor - Silver, Larry (Princeton University Press, 2008)
Introduction : Maximilian's artworlds -- Family ties : genealogy as ideology for Emperor Maximilian I -- Translation of empire -- Caesar Divus : leader of Christendom -- Shining armor : Emperor Maximilian, chivalry, and war -- Magnificence and dignity : princely pastimes -- Conclusions : dynasty and/or nation?